Research Management in Virtual Organization between Higher Education and Industry for Developing Lecture’s Knowledge - Achlison, Unang; Mufadhol, Mufadhol (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
Lecturers adapt to technology rises because the industries have improved business practices and implemented process changes to become more sustainable. The technological innovations can be generated by research projects that can yield useful innovations in industry. Lecture’s research in higher education becomes a fundamental need that must be managed sustainability. The policy and strategy in research between higher education and industry will enhance the quality and sustainability of higher education. The concept of research management in virtual organization adopted from a triangular model that related to higher education, industry, and government. The relationship can serve as a model that can adapt technology in industries and develope lecture’s knowledge. The research management in virtual organization used in this research is employing direct observation for problem identification and assigning the Internet service requirement and the availability of hardware and software resources. Developing lecture’s knowledge by considering polytechnic’s lecture becomes the main objective. The implementation of research management in virtual organization allows (1) industry’publish project themes, (2) lecturers can download the project themes as idea, and (3) lecturers submit proposal documents. The data survey are processed with the correlation, scale reliability, and validity analysis by using SPSS 16.0. Based on data survey result, the all indicators of lectiure’s knowledge development have positive values and significant correlations.